Faktor-Faktor yang Berpengaruh Terhadap Kebijakan Hutang Perusahaan (Studi Kasus pada Sub Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024) - Aprilyanti, Savira Nur; Gantino, Rilla (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to examine the effect of profitability, sales growth, and liquidity on debt policy in property and real estate companies listed on the Indonesia Stock Exchange for the 2019–2024 period. The independent variables in this study include profitability, measured by Return on Assets (ROA); sales growth (SG); and liquidity, measured by the Current Ratio (CR). Meanwhile, the dependent variable is debt policy, measured by the Debt-to-Equity Ratio (DER). This study uses a quantitative approach, employing multiple linear regression analysis. The sample comprises 174 observational data points collected using purposive sampling. Testing was conducted using SPSS software, which includes the classical assumption test, the coefficient of determination test, the simultaneous test (F test), and the partial test (t test). The results show that profitability, sales growth, and liquidity simultaneously significantly affect debt policy. Partially, profitability tends to be positive, sales growth tends to be negative but not significant with respect to debt policy, while liquidity has a simultaneous negative effect. Of the four hypotheses proposed, two were accepted, and two were rejected because the direction of the influence did not match the initial assumption, and the significance value was more than 0.05.